When the unexpected happens: Isolated fallopian tube torsion with large hematosalpinx mistaken for ovarian cyst torsion in a pediatric patient: A case report (Indian Journal of Case Reports, 2025)
Isolated fallopian tube torsion (IFTT) in adolescent girls is an infrequent but significant cause of acute abdominal pain in gynecology, often misdiagnosed as ovarian torsion. A 13-year-old unmarried virgin girl presented to the gynecological outpatient department with acute abdominal pain lasting 5 days, accompanied by nausea, vomiting, and fever for 2 days. Pelvic ultrasound revealed a normally sized uterus and a normal right ovary, while the left ovary was slightly enlarged (4 × 5 cm) and displaced medially, demonstrating a “whirlpool sign” indicative of vascular pedicle twisting, suggestive of left ovarian torsion. A large exophytic lesion measuring 8 × 6 cm was also noted in the left adnexa, raising concerns for a left exophytic or paraovarian cyst. Given her clinical presentation, the patient underwent an emergency laparotomy. Intraoperative findings revealed minimal hemoperitoneum (50–80 mL), a normally sized uterus deviated to the left, and a left fallopian tube tightly twisted 3 times, with large hematosalpinx (8 × 6 cm), distended with clots. Due to complete damage to the left fallopian tube, left salpingectomy was performed, with histopathological examination confirming hematosalpinx. Hence although IFTT is uncommon, it should be included in the differential diagnosis for acute abdominal pain in young girls and women of reproductive age. Early recognition and prompt surgical intervention are crucial to prevent complications and preserve tubal function.